Impact of Promotion on Profitability of an Organisation: A Study of Nigerian Bottling Company PLC - Anthonia, Uloko (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
The study assesses the impact of promotion on the profitability of the Nigeria Bottling Company Plc, Enugu Plant. The population of the study was made up of 56 management staff drawn from marketing, sales and accounting/finance departments of the company. Employing a census technique, the whole population of 56 management staff constituted the sample size of the study and data obtained from the 56 copies of the questionnaire were presented using descriptive statistics whereas, multiple regression analysis with the aid of the Statistical Package for Social Science (SPSS) was conducted to test both the company’s financial statement from the year 2003 to 2012 and the hypotheses. The findings from data analysis of company’s financial statement shows that, profit is slightly influenced by the variables of sales income not necessary cost of promotion, while the results of the hypotheses testing indicated that, advertising has no significant impact on profitability; sales promotion has a significant impact on profitability; personal selling has no significant impact on profitability; public relations has a significant impact on profitability. The need for an organization to properly coordinate its promotional strategies to achieve a clear consistent and competitive message about itself and its products has become an issue of concern to every result driving firm. The study concluded that, promotion is an important tool that helps companies to improve their profitability. We recommended that there is the need for organizations to increasingly integrate effective promotion in their activities to improved their profitability and competitive advantage.